Pelatihan Perencanaan Pembelajaran Merdeka Belajar di SMP Kelas VII pada Konteks Pencaharian Harta Karun di Sungai Musi - Malalina Malalina; Ratu Ilma Indra Putri; Zulkardi Zulkardi; Rita Inderawati; Elika Kurniadi; Lisnani Lisnani; Chika Rahayu; Rini Herlina; Dewi Rawani; Tria Gustiningsi; Artika Sari; Delia Septimiranti (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2021)
This activity is carried out to provide understanding to teachers related to independent learning planning. Apart from that, to train teachers in making lesson plans using the context in the surrounding environment. The environmental context can be used for the learning process to understand more real concepts or subject matter. The method used is lecture, question and answer and practice. The result of this service activity is an understanding related to the preparation of independent learning learning plans for middle school teachers in Pagar Alam, South Sumatra using the existing context in the environment. Apart from that, all training participants can show a good response and improve teacher professionalism.